LABORATORY ANALYSIS OF BLOOD IN PREGNANT WOMEN WITH PRE-ECLAMPSIA IN THE DELIVERY ROOM OF RSUD DR. R. KOESMA TUBAN. - Umu Qonitun; Miftahul Munir; Lilik nur hidayah (Indonesian Midwifery and Health Sciences Journal, 2023)
30-40% of maternal deaths in Indonesia were caused by pre-eclampsia in 2018. Preeclampsia is a specific syndrome in pregnancy that can cause liver problems. Disorders can be characterized by abnormal laboratory results in the liver enzymes while in the kidney is indicated by the presence of proteinuria. Organ disorders can cause morbidity and death of the mother and fetus. This study aims to analyze the results of blood laboratory in pregnant women with preeclampsia in the delivery room of RSUD dr.R Koesma Tuban in 2020. Method: The research design is correlation analysis. The population of all pregnant women with preeclampsia in the delivery room at RSUD dr. R Koesma Tuban from January to June 2020, with a total of 102 people, a sample of 52 people used simple random sampling. The independent variable is preeclampsia, the dependent variable is the platelet level. Using the chi square test with a significance level of p<0.05. Results: most of the pregnant women with severe preeclampsia 39 (75%), almost all 42 (81%) platelet levels were in the normal category. With a significance value of 0.115, then H1 is rejected, meaning that there is no relationship between platelet laboratory levels in pregnant women and preeclampsia in the maternity ward of RSUD DR. Koesma Tuban. Conclusion: there is no relationship between preeclampsia and platelet levels. So that it is hoped that research can be carried out on the causes of preeclampsia and other laboratory results